Biology and Gender in the Labor Market - Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2016)
Can biology help us to better understand gender differences in labor market behavior and outcomes? This chapter reviews the emerging literature which sheds light on this question, considering research in four broad areas: i) behavioral endocrinology; ii) human genetics; iii) neuroeconomics; and iv) sensory functioning and time-space perceptions.
Keywords: J31; A12; Z0; 330; gender wage gap; labor market outcomes; human biology; neuroeconomics; behavioral genetics